Reflexões sobre a formação do professor de matemática: investigando a prática de ensino no curso de licenciatura da UFPA - MENDES, Maria José de Freitas (Universidade Federal do Pará, 2012)
The aim of this study is to investigate the process of formation of the mathematics teacher. The target of this study lies in the contribution on the subject teaching training of mathematics on the formation of teachers facing the new paradigms of formation with professional development and as a reflexive teacher. The study involved three undergraduate students of Mathematics from Universidade Federal do Pará (UFPA), during the development of the subject teaching traing of mathematics and the teachers from the school where these students were training who were in continuos formation enroled on a graduate program of specialization at Universidade Federal do Pará (UFPA). The basic material for this study was gotten through semi-structured interviews, etnographic reports and observation carried out with activities at Núcleo Pedagógico de Apoio ao Desenvolvimento Científico (NPADC) and at public schools in Belém. Besides describing and contextualizing historically courses of formation teachers, it also analyses the separation theory-practice clearly seen on those courses, and the lack of pedagogical and epistemology focus on the contents to be worked. Results show the need to be given a more pratical look at the pedagogical formation at undergraduate courses, leading the future teachers to develop autonomous, reflexive and investigative attitudes towards teaching.